The art show attacks! - Chabert, Jack (Chabert, Jack. Eerie Elementary, 2018)
Sam is working on making a clay dinosaur for the school art show and sale when the clay suddenly comes to life and attacks him, a sure sign that once again Orson Eerie, whose spirit inhabits the school, is up to something--and it is up to Sam, Antonio, and Lucy, to discover how a self-portrait of Orson figures into his evil plan.